The irrigation rehabilitation project = (The World Bank in Vietnam (WB), 2003)
The Irrigation Rehabilitation Project will restore or establish sustainable irrigation service by rehabilitation and completion of infrastructure and improvement of operation and maintenance in selected irrigation schemes. The project will therefore increase agricultural production (primarily of rice for food) and farmer incomes, and reduce poverty in selected rural areas of Viet Nam. The project will include: (a) rehabilitation and completion of seven irrigation schemes comprising a gross area of around 130,000 ha located in the south, central and northern regions of Viet Nam; (b) institutional development; and (c) resettlement and rehabilitation of families whose land and/or assets are acquired by the state for the project.